1998
DOI: 10.1002/(sici)1098-2396(199811)30:3<318::aid-syn9>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Cellular electrophysiological effects of chronic fluoxetine and duloxetine administration on serotonergic responses in the aging hippocampus

Abstract: The pharmacological and physiological effects of chronic administration of the selective serotonin (5-hydroxytryptamine, 5-HT) reuptake inhibitor (SSRI) fluoxetine and the dual 5-HT/norepinephrine (NE) reuptake inhibitor duloxetine were compared on 5-HT-mediated electrophysiological responses recorded in the hippocampus of young (3-5 months) and old (17-20 months) female Fischer 344 rats. Fluoxetine, duloxetine, or vehicle (saline) was administered once daily for 14 days (10 mg/kg, i.p.) and extracellular reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…For example, it has been shown that duloxetine may also affect vascular tone in the lower urogenital tract [44]. Moreover, the previous studies of duloxetine in the lower urinary tract involved acute treatment only, and studies in the CNS suggest that certain effects of duloxetine may differ upon chronic treatment [36,45,46]. A recent preliminary report on healthy human females shows that a single dose of duloxetine (40 mg) did not affect basal urethral resistance, but increased the pressure amplitude responses to sacral magnetic stimulation [47].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…For example, it has been shown that duloxetine may also affect vascular tone in the lower urogenital tract [44]. Moreover, the previous studies of duloxetine in the lower urinary tract involved acute treatment only, and studies in the CNS suggest that certain effects of duloxetine may differ upon chronic treatment [36,45,46]. A recent preliminary report on healthy human females shows that a single dose of duloxetine (40 mg) did not affect basal urethral resistance, but increased the pressure amplitude responses to sacral magnetic stimulation [47].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Following 5-HT application, RT 50 values were significantly increased in both young and old fluoxetine-treatment groups, but not in chronically treated duloxetine groups. These different patterns of recovery may be due to the differences in reuptake profile of fluoxetine vs. duloxetine (62). In a similar model of aging, microiontophoretically applied 5-HT in the hippocampus increased sensitivity to microiontophoretically administered duloxetine with increasing age (64).…”
Section: Duloxetine In Models Of Agingmentioning
confidence: 99%